1975
DOI: 10.1093/ajcp/64.3.304
|View full text |Cite
|
Sign up to set email alerts
|

Hepatocellular Carcinoma and Intermediateα1-Antitrypsin Deficiency (MZ Phenotype)

Abstract: A case history of a 16-year-old boy with hepatocellular carcinoma and an intermediate deficiency of alpha1-antitrypsin (MZ phenotype) is presented. Previous reports have suggested that hepatocellular carcinoma may be associated with the Z variant of antitrypsin and either a severe or intermediate antitrypsin deficiency. The present case is unusual because of the rather high level of the serum trypsin inhibitory capacity for an MZ heterozygote (1.633 units), which may be due to involvement of the liver by the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0
1

Year Published

1977
1977
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 0 publications
0
21
0
1
Order By: Relevance
“…However, in two reports the bodies have been identified in the neoplastic cells of hepatocellular carcinomas-in a single case (Lieberman et al, 1975), and in 10 of the 17 liver cell carcinomas described by Palmer and Wolfe (1976) (1976), we considered the indirect peroxidase method to be inferior to the others. Our trial also showed a difficulty apparently not experienced by others: abnormal livers contain a large amount of brown pigment (lipofuscin, ceroid, and bile pigments) and we found it difficult to distinguish with confidence between these and the brown colour produced by the diamino-benzidine customarily used to demonstrate the peroxidase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in two reports the bodies have been identified in the neoplastic cells of hepatocellular carcinomas-in a single case (Lieberman et al, 1975), and in 10 of the 17 liver cell carcinomas described by Palmer and Wolfe (1976) (1976), we considered the indirect peroxidase method to be inferior to the others. Our trial also showed a difficulty apparently not experienced by others: abnormal livers contain a large amount of brown pigment (lipofuscin, ceroid, and bile pigments) and we found it difficult to distinguish with confidence between these and the brown colour produced by the diamino-benzidine customarily used to demonstrate the peroxidase.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma occurs commonly in patients with PiZZ phenotype andcirrhosisorhepatic fibrosis (Berg and Eriksson, 1972) and has been reported in patients with PiMZ phenotype (Rawlings et al, 1974;Lieberman et al, 1975). Norkin and Campagna-Pinto (1968) described globular hyaline 135 inclusions in eight of 81 cases of hepatoma; these were periodic acid Schiff positive, but they had two characteristics which al-antitrypsin bodies do not: they were visible as hyaline masses in haematoxylin and eosin preparations, and they were extracellular as well as intracellular.…”
Section: Discussionmentioning
confidence: 99%
“…Recent review articles (Feld 1989;Gourley et al 1989) and research articles (Sandford et al 1999;Sigsgaard et al 2000) provide documentation that both carriers (PiMS and PiMZ) and deficiency allele combinations (PiSS, PiSZ, and PiZZ) are at risk for various adverse health effects. The adverse health effects associated with being a carrier of the PiS defective allele were reviewed in 1989 (Gourley et al 1989), and they included cirrhosis (Lieberman et al 1975), multiple sclerosis (Lolin and Ward 1995), chronic "cryptogenic" liver disease (Carlson and Eriksson 1985), and malignant hepatoma (Carlson and Eriksson 1985). In addition, there are more recent reports that the PiMS phenotype can be associated with hepatic dysfunction during the first 6 months of life (Pittschieler 1994), to cryptogenic cirrhosis between ages 1 month and 18 years (Lima et al 2001), and intracranial arterial dissections (Schievink et al 1998).…”
Section: Att Deficiency and Healthmentioning
confidence: 99%
“…The sections were then examined for PASpositive inclusion globules. In patients with H1CC and AAT deficiency, PASpositive diastase-resistant globules are found in the malignant hepatocytes as well as in the non-tumorous liver tissue (Lieberman et al, 1975 (Prinsloo and Turnbull, unpublished).…”
mentioning
confidence: 98%
“…The latter takes the form of cholestatic jaundice in infancy (neonatal hepatitis), childhood cirrhosis and, less often, cirrhosis in adults. In addition, a few cases of hepatocellular (11CC) or cholangiocellular cancer have been described in patients with homozygous (ZZ) or heterozygous (MZ) AAT deficiency (Ganrot et al, 1967;Accepted 29 December 1977 Berg and Eriksson, 1972;Eriksson and Hiagerstrand, 1974;Aagenaes et al, 1974;Lieberman, 1974;Rawlings, et al, 1974;Williams and Fajardo, 1974;Lieberman et al, 1975;Zwi et al, 1975). A characteristic finding in individuals with both homozygous or heterozygous AAT deficiency, in the presence or absence of liver disease, is the accumulation of periodic acid-Schiff (PAS)-positive, diastase-resistant globules in periportal hepatocytes (Sharp, 1971).…”
mentioning
confidence: 99%